Alternative Journalism and its Media Content - Al-Kubaisi, Suhaf Ali Hussein (Journal of Ecohumanism, 2024)
This research aims to find out the directions of alternative journalism for the production of media contents from the point of view of Iraqi journalists. The research relied on the descriptive survey method and an electronic questionnaire form, which was distributed to a deliberate sample of Iraqi journalists, numbering 300 individuals. One of the most important results of the research is: the competition and the struggle is clear between the traditional media and the journalist, and the employment of modern technologies in the liberation of the press report, and the journalist has a device from the journalists. A and courage and excitement that distinguishes their contents, and from the power that affects all fields, and to raise the media product, and that The digital revolution and the technological development contributed to the growth of the phenomenon of the physical journalism and made the news quick access, and it has become published in different patterns and forms that attract follow-up and increase his confidence in them.